Strengthening Early Childhood Collaborative Skills through Malay Ethnopedagogy: A Qualitative Descriptive Approach - Azlin Atika Putri (Jurnal Pelita PAUD, 2025)
The purpose of this study is to outline the ways in which Al Mahira Kindergarten in Rumbai, Pekanbaru City, uses Malay ethnopedagogical principles to improve the cooperative abilities of its five to six-year-old students. Important early childhood competences include collaborative skills like teamwork, role sharing, respecting peers' ideas, and problem solving. Early findings, however, suggest that young children continue to exhibit traits such as egocentrism, role-competing, and trouble settling disputes with their peers. Seventeen youngsters between the ages of five and six served as the subjects of this qualitative descriptive study. Visual documentation, semi-structured interviews with educators and caregivers, and participant observation were used to gather data. Through data reduction, data presentation, and conclusion drawing/verification, data analysis was carried out interactively. The study's findings demonstrated that incorporating Malay ethnopedagogical values—like tolerance, politeness, deliberation, and mutual cooperation—into play activities, group projects, and casual conversations greatly enhanced kids' capacity for teamwork. Of the 17 kids, 76.5% showed that they could support their peers, 64.7% could respect differences of opinion, 70.6% could share tasks during activities, and 58.8% could work together to solve difficulties. These results demonstrate that Malay ethnopedagogy is a successful pedagogical approach to fostering cooperation in early childhood education, in addition to its significance in conserving local culture.